Intracranial Pressure and Cerebral Perfusion Pressure in Large Spontaneous Intracranial Hemorrhage and Impact of Minimally Invasive Surgery - Al-Kawaz, Mais N.; Li, Yunke; Thompson, Richard E.; Avadhani, Radhika; de Havenon, Adam; Gruber, Joshua; Awad, Issam; Hanley, Daniel F.; Ziai, Wendy (Frontiers in Neurology, 2021)
Introduction: We investigated the effect of hematoma volume reduction with minimally invasive surgery (MIS) on intracranial pressure (ICP) and cerebral perfusion pressure (CPP) in patients with large spontaneous intracerebral hemorrhage (ICH). Methods:Post-hoc analysis of the Minimally Invasive Surgery Plus Alteplase for Intracerebral Hemorrhage Evacuation (MISTIE III) study, a clinical trial with blinded outcome assessments. The primary outcome was the proportion of ICP readings ≥20 and 30 mmHg, and CPP readings <70 and 60 mm Hg. Secondary outcomes included major disability (modified Rankin scale >3) and mortality at 30 and 365 days. We assessed the relationship between proportion of high ICP and low CPP events and MIS using binomial generalized linear models, and outcomes using multiple logistic regression. Results: Of 499 patients enrolled in MISTIE III, 72 patients had guideline based ICP monitors placed, 34 in the MIS group and 38 in control (no surgery) group. Threshold ICP and CPP events ≥20/ <70 mmHg occurred in 31 (43.1%) and 52 (72.2%) patients respectively. On adjusted analyses, proportion of ICP readings ≥20 and 30 mmHg were significantly lower in the MIS group vs. control group [Odds Ratio (OR) 0.27, 95% Confidence Interval [CI] 0.11–0.63 (p = 0.002); OR = 0.18, 0.04–0.75, p = 0.02], respectively. Proportion of CPP readings <70 and 60 mm Hg were also significantly lower in MIS patients [OR 0.31, 95% CI 0.15–0.63 (p = 0.001); OR 0.30, 95% CI 0.11–0.83 (p = 0.02)], respectively. Higher proportions of CPP readings <70 and 60 mm were significantly associated with short term mortality (p = 0.04), and (p = 0.006), respectively. Long term mortality was significantly associated with higher proportion of time with ICP ≥ 20 (p = 0.04), ICP ≥ 30 (p = 0.04), and CPP <70 mmHg (p = 0.01). Conclusion: Our results are consistent with the hypothesis that surgical reduction of ICH volume decreases proportion of high ICP and low CPP events and that these variables are associated with short- and long-term mortality.